Encapsulation of clotrimazole into solid lipid nanoparticles by microwave-assisted microemulsion technique. (December 2016) - Shah, Rohan M.; Eldridge, Daniel S.; Palombo, Enzo A.; Harding, Ian H.
Highlights: SLNs are an attractive alternative to traditional colloidal carriers. Microwave-assisted procedure employed in production of clotrimazole-loaded SLNs. SLNs exhibited a gradual and sustained release (<70%) of clotrimazole after 24 h. Clotrimazole release governed by both Fickian diffusion and non-Fickian mechanisms. Negligible cytotoxicity of SLNs and easily taken up by human cells. Abstract: Recently, we reported a novel microwave-assisted one-pot microemulsion procedure for the production of solid lipid nanoparticles (SLNs). In the current study, the suitability of the microwave-assisted procedure in encapsulation of clotrimazole was investigated. Clotrimazole, a synthetic, imidazole-type anti-fungal drug, was used as lipophilic model drug. The particle sizes of microwave-produced stearic acid-based clotrimazole-loaded SLNs were within the nanometer size range with zeta potential values high enough to predict good physical stability. High encapsulation efficiency and loading capacity demonstrated the high encapsulation capability of microwave-produced SLNs. Physicochemical characterization of SLNs and bulk stearic acid, performed by differential scanning calorimetry (DSC) and X-ray diffraction (XRD), indicated decreased crystallinity of stearic acid, a factor that influences incorporation and release of drug. The release studies demonstrated a slow and sustained but incomplete release of drugs (<50% after 12 h and <70% after 24 h). The release of clotrimazole was found to be governed by both diffusion and swelling, i.e. anomalous or non-Fickian diffusion. The release data, however, fitted more appropriately to the Weibull model. The clotrimazole-loaded SLNs were found to be non-toxic, investigated by cell viability assays using human epithelial A549 and mouse epithelial 3T3-L1 cell lines. The cytotoxic concentration (CC50 ) value was greater than 100 μg/mL. Internalization of SLNs into A549 cells by endocytosis was demonstrated by confocal imaging. The antifungal efficacy of drug-loaded SLNs was evaluated on Candida albicans . These encouraging results suggest that microwave-produced SLNs can be considered as efficient carriers for clotrimazole and will further assist their development for administration via different routes.